Banks' portfolio similarity during the COVID-19 pandemic - Dongwoo Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: This study tries to identify the impact of the COVID-19 pandemic on the similarity of banks' loan portfolios. Design/methodology/approach: Using the entire firm-level bank loan data from 2009 to 2020 in the Korean market, this study analyzes the cosine similarity in terms of credit rating, industry, and region between banks. Findings: The study discovered that interbank portfolio similarity has escalated over time, with the similarity notably intensifying during the COVID-19 pandemic. Additionally, it was found that larger banks exhibit greater similarities, a trend that has become increasingly pronounced during the pandemic period. Research limitations/implications: This study provides empirical evidence of the synchronization in lending behaviors among major South Korean banks during the COVID-19 pandemic. It posits that while the synchronicity of banks' lending patterns during typical financial crises is generally accepted, further research in financial markets of other countries is necessary to substantiate this claim universally. Originality/value: Therefore, the role of financial authorities to alleviate deepening interbank portfolio synchronization triggered by the COVID-19 pandemic and the resulting escalation of financial market instability is emphasized.
Keywords: 650; Portfolio similarity; COVID-19; Corporate loan; Credit rating; industry; Region